Squamous cell carcinoma of the cervix simulating an advanced malignancy of the ovaries (1998)
A 40-year-old woman was diagnosed as having stage II squamous cell cervical carcinoma and managed with radiotherapy. Three months after treatment, she presented with features suggestive of an advanced ovarian tumour including gross abdominal swelling, bilateral ovarian tumours, multiple tumour seedlings in the abdominal cavity and ascites. There was also pleural effusion. Operative findings revealed widespread intra-abdominal metastases whose histology, contrary to expectations, showed squamous cell carcinoma of cervical origin. Distant metastases from squamous cell carcinoma of the cervix are rare. A high index of suspicion is necessary to detect this unusual mode of presentation.